PIM gender research: 2017 in review - Crimi, Gabriella (International Food Policy Research Institute, 2019)
The CGIAR Research Program on Policies, Institutions, and Markets (PIM) has emphasized gender analysis across its research activities. Investing in research and initiatives that seek to foster gender equality and women’s empowerment is essential to realizing the full potential of agriculture as an engine of economic growth, poverty reduction, and development. As such, a critical reflection on gender analysis within PIM’s outputs not only serves the program’s gender strategy but also is instrumental to achieving PIM’s goals of a food-secure present and future. This review examines 133 PIM peer-reviewed publications in 2017 to identify key lessons learned and highlight best practices for research that engaged with gender analysis. Outputs analyzed include published journal articles, book chapters, and books. Although including gender analysis in every project may not be feasible or plausible, this review highlights some places where research questions may be expanded to include gender analysis. Ultimately, research that incorporates gender analysis helps produce better policy and may have a positive impact on development outcomes.